2016
DOI: 10.1186/s40561-016-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Video-based learning ecosystem to support active learning: application to an introductory computer science course

Abstract: The systematic use of technologies in order to orchestrate learning has become widely used in the past years. Diverse technologies have been applied in a variety of teaching practices; for instance learning tools which allow you to flip the classroom or monitor other active learning practices. However, the developed systems are only a subset of different kinds of learning materials and learning tools that an educator should take into consideration; and most importantly they do not offer an overview of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 13 publications
4
28
0
2
Order By: Relevance
“…Instructors also need to evaluate the instructional effectiveness and value of learning resources, ensuring those selected align to the given context, curriculum, and outcomes, and instructors must adjust materials based on credibility, clarity, validity, reliability, accuracy, currency, accessibility, usability, and quality of course resources (Varvel, 2007). Advanced interactive video assessment tools help shift passive learning into active knowledge construction, where students interact with video lectures through embedded question checks, and instructors track data on students' viewing and responses to questions (Chen & Wang, 2016;Giannakos, Krogstie, & Aalberg, 2016).…”
Section: Elements Of Course Designmentioning
confidence: 99%
“…Instructors also need to evaluate the instructional effectiveness and value of learning resources, ensuring those selected align to the given context, curriculum, and outcomes, and instructors must adjust materials based on credibility, clarity, validity, reliability, accuracy, currency, accessibility, usability, and quality of course resources (Varvel, 2007). Advanced interactive video assessment tools help shift passive learning into active knowledge construction, where students interact with video lectures through embedded question checks, and instructors track data on students' viewing and responses to questions (Chen & Wang, 2016;Giannakos, Krogstie, & Aalberg, 2016).…”
Section: Elements Of Course Designmentioning
confidence: 99%
“…• computer science (Fetaji, Fetaji, Sukic, Gylcan, & Ebibi, 2016;Giannakos, Krogstie, & Aalberg, 2016;Reza & Ijaz Baig, 2015); • English language instruction (Yang, 2017); • engineering (Kecskemety, Corrigan, & Abrams, 2015;Lucke, Dunn, & Christie, 2017;Yelamarthi, K., Drake, E., & Prewett, 2016;Yusong & Daher, 2017); • operations management (Asef-Vaziri, 2015;Pragman, 2014;Prashar, 2015); • pharmacy (Cotta, Shah, Almgren, Macías-Moriarity, & Mody, 2016;Ferreri & O'Connor, 2013;Patanwala, Erstad, & Murphy, 2017); • psychology (Hudson et al, 2015;Talley & Scherer, 2013;Wilson, 2013);…”
Section: Introductionmentioning
confidence: 99%
“…Using a simulation software can help students to increase their motivation and the ability to learn in a non-threatening environment (Blakely et al, 2009). However, using interactive simulations can be an important cognitive burden, hindering the learning process Video simulations have demonstrated that they can be used to prepare students for a real working environment, making them feel more secure and support active learning (Del Blanco et al, 2017;Giannakos et al, 2016). The Pocket Nurse 1 organization provides equipment and software for simulation in healthcare education.…”
Section: Background and Related Workmentioning
confidence: 99%